CLASSIFICATION ASPECTS OF RATIONAL UTILIZATION OF POLYMER COMPOSITE MATERIALS IN THE CIVIL AIRCRAFT STRUCTURES - Haidachuk, Oleksandr; Bo, Wang; Bychkov, Serhii; Andrieiev, Oleksii (Proceedings of National Aviation University (archive), 2019)
The article analyzes the classification aspects of the rational choice of the polymer composites types for aircraft structures. Based on the analysis, criteria for the effective selection of polymer composite materials are proposed taking into account various factors operating in the production. The problem is formulated on the need to develop an effective method for assessing the choice of polymer composites for aircraft structures. The article analyzes the classification aspects of the rational choice of the polymer composites types for aircraft structures. Based on the analysis, criteria for the effective selection of polymer composite materials are proposed taking into account various factors operating in the production. The problem is formulated on the need to develop an effective method for assessing the choice of polymer composites for aircraft structures. <!–[if gte mso 9]> 800x600 <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false UK X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Обычная таблица"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:"Times New Roman"; –> <!–[endif] –>